The Influence of Green Product and Green Promotion on Purchase Intention: The Mediating Role of Green Brand Image - Meivianto, Muhammad Tajuddin; Pradana, Bayu Ilham (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effects of green products and green promotion on consumers' purchase intention, with green brand image serving as a mediating variable, in the context of Fore Coffee in Malang City. Design/methodology/approach – This study employs a quantitative research approach. The population consists of individuals residing in Malang City who are familiar with Fore Coffee. Using a non-probability sampling method with a purposive sampling technique, data were collected from 138 respondents. The proposed research model was analyzed using Partial Least Squares (PLS) to examine both the direct and indirect relationships among the variables. Findings – The results reveal that green products do not have a significant direct effect on purchase intention, whereas green promotion and green brand image positively and significantly influence purchase intention. In addition, both green products and green promotion significantly enhance green brand image. The mediation analysis indicates that green brand image fully mediates the relationship between green products and purchase intention and partially mediates the relationship between green promotion and purchase intention. Originality/value – This study contributes to the green marketing literature by demonstrating the mediating role of green brand image in explaining how green products and green promotion influence purchase intention. The findings provide practical insights for coffee shop businesses in developing effective sustainability-oriented marketing strategies that strengthen brand image and encourage consumer purchasing behavior.